Economic Efficiency and Political Capture in Public Service Contracts1. (27th April 2017) - Gagnepain, Philippe; Ivaldi, Marc
Abstract : We consider contracts for public transport services between a public authority and a transport operator. We build a structural endogenous switching model where the contract choice results from the combined effects of the incentivization scheme aimed at monitoring the operator's efficiency and the political agenda followed by the regulator to account for the voice of private interests. Our results support theoretical predictions as they suggest that cost‐plus contracts entail a higher cost for society than fixed‐price contracts but allow the public authority to leave a rent to a subset of individuals. Accounting for transfers to interest groups in welfare computations reduces the welfare gap between cost‐plus and fixed‐price regimes.